Using Topological Properties to Measure the Strength of Co-authorship Ties - Brandão, Michele A.; Diniz, Matheus A.; Moro, Mirella M. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM); 2016: Anais do V Brazilian Workshop on Social Network Analysis and MiningDO - 10.5753/brasnam.2016.6455, 2016)
Studying the strength of ties in social networks allows to identify impact at micro-macro levels in the network, to analyze how distinct relationships play different roles, and so on. Indeed, the strength of ties has been investigated in many contexts with different goals. Here, we aim to address the problem of measuring ties strength in co-authorship social networks. Specifically, we present four case studies detailing problems with current metrics and propose a new one. Then, we build a co-authorship social network by using a real digital library and identify how the strength of ties relates to the quality of publication venues when measured by different topological properties. Our results show the best ranked venues have similar patterns of strength of co-authorship ties.